Increasing Mathematics Learning Outcomes on Fraction Materials Through Discovery Learning Model - Syarifudin, Imam (Universitas Sebelas Maret, 2020)
Mathematics subject matter of fractions with the Discovery Learning learning model. The research conducted was Classroom Action Research with 2 cycles, with each cycle consisting of 2 meetings. Each cycle includes the stages of planning, implementation, observation and reflection. Each meeting was conducted pre-test and post-test to determine the progress of students. In Cycle I, students who completed the post test were 68.18%. In Cycle II, the students who completed the post test were 90.91%. From the implementation of these 2 cycles, it is shown that the Discovery Learning model can improve the learning outcomes of students in Mathematics in Class V fractions.